Pemanfaatan Aplikasi Benime untuk Pembelajaran Mufradat Siswa Kelas 1 di MIN 1 Solok - Amrina, Amrina; Mudinillah, Adam; Ulya, Fadilatu (Arabia, 2021)
AbstractThis researcher aims to introduce the application of Benime in the subject of Mufradat. Which mufradat is the main concept for learning Arabic and part of the science of Arabic language that expresses with respect to the objectification of a word and also one of the elements that should be mastered in learning about a foreign language. With this Benime application Mufradat will be displayed in the form of Video and there are sounds and animations to attract learners in learning Mufradat. This study uses a quantitative research method which is a type of pradigm research, a quantitative approach based on the paradigm in which the research is able to plan and realize the transition about the world around. In this case, the object of research is 1st grade students in MIN 1 solok. The results of this study provide great benefits to improve the unique ability of learners. In accordance with what was presented by the Arabic language teacher, that this Benime application is very helpful in providing lesson materials, because the video created contains animated elements and is in accordance with the textbook.